Signaling roadmap to epithelial–mesenchymal transition in pterygium, TWIST1 centralized. Issue 10 (7th March 2019) - Meshkani, Seyed Elyas; Kooshan, Narges; Moghadam, Arezoo Baradaran; Falanji, Farahnaz; Adli, Abolfazl; Baghbani‐Arani, Fahimeh; Arian, Alireza Ghasemi; Rad, Abolfazl
Abstract: Pterygium as a complex disease shares common features with other malignant cells in its onset recurrence and especially epithelial–mesenchymal transition (EMT) transition. Although using different approaches including conjunctival autografts, amniotic membrane, radiotherapy, mitomycin C (MMC) has shown promising insights in the inhibition of pterygium recurrence, it needs to be investigated in more details in molecular pathways to present adjuvant target therapy. In this study, we aimed to evaluate the expression of and then illustrate the role of signaling pathways on EMT in pterygium. Using real‐time polymerase chain reaction, the twist‐related protein 1 (TWIST1 ) expression was compared in primary pterygium and normal conjunctiva. This study assessed the mRNA expression, as well as the association between the clinicopathological indices and the gene expression level. The expression level of TWIST1 was overexpressed in 36% of our cohort ( n  = 76). There was a significant positive correlation between recurrence with grade T, grade V and a significant negative correlation with growth activity. Our vast literature review on different signaling pathways in pterygium showed that EMT has centralization role in recurrence of this disease. Our data confirmed that EMT is important in the recurrence of pterygium samples and different signaling pathways end up activating the EMT markers. It is suggested to evaluate the environmental factors and their correlation with molecular markers to select favorable treatment for this kind of diseases. Abstract : Eepithelial–mesenchymal transition (EMT) is one of the main signaling pathways in pterygium. TWIST1 is centralized in EMT and overexpressed in pterygium individual which has recurrence. Recurrence has significant positive correlation with grade T and grade V in pterygium.